BEASISWA LPDP SEBAGAI INVESTASI PENDIDIKAN: EVALUASI AKSESIBILITAS, KONTRIBUSI ALUMNI, DAN PEMERATAAN PEMBANGUNAN SDM - Hayati, Hazimah Dzikra; Rahmawati, Milatul; Hadiyanto, Hadiyanto; Yahya, Yahya (STKIP Pesisir Selatan, 2025)
This study aims to evaluate the effectiveness of the LPDP (Indonesia Endowment Fund for Education) scholarship program in promoting equitable access to higher education, alumni contributions to national development, and the fair distribution of high-quality human resources (HR). Utilizing the CIPPO (Context, Input, Process, Product, Outcome) evaluation model, the research examines policy documents, LPDP annual reports, academic journals, and alumni testimonials. Findings reveal that while LPDP plays a strategic role as an educational investment instrument, it still faces challenges in accessibility, the effectiveness of affirmative action for underdeveloped regions, and a weak alumni tracer system. Despite successful alumni contributing to public, educational, and social sectors, their impact remains unstructured and untracked. Policy reform is recommended, including context-based selection criteria, robust post-study monitoring systems, and strengthened synergy among LPDP, local governments, and higher education institutions to ensure equitable and sustainable national human development.